Simulating Predator-Prey System by Cellular Automata - Kunis, Fabien Teofanis; Dimitrov, Martin; Markova, Desislava (Open Schools Journal for Open Science, 2022)
Our work explores the possibilities of using cellular automata to simulate the predator-prey interaction. A cellular automaton is a discrete model that allows it to be used for various computational purposes. In recent years, we have observed how important it is to know the behaviour of various biological and ecological systems. Knowledge of the behaviour and evolution of different biological and ecological systems will allow us to adapt more quickly to different possible scenarios. Our work aims to simulate the behaviour of a predator-prey system using cellular automata and get realistic data from the simulation.